Peran NGO Sikkola Rakyat dalam Memberikan Literasi Dasar di Rumah Belajar Starban - Panjaitan, Nicolas; Bengkel (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
as well as digital, financial, scientific, cultural, and civic literacy, are essential skills for children's academic and social development. However, in many regions, especially in marginalized areas, basic literacy rates remain low. Financial pressures that force children to contribute to their family's livelihood, as well as a lack of community participation in creating a child-friendly environment, make it difficult for children to acquire basic literacy skills. Factors such as limited access to educational facilities, a shortage of qualified teachers, and a lack of reading materials are major obstacles to improving children's literacy. In facing these challenges, NGOs play an important role in providing alternative solutions to improve children's basic literacy skills. This research was conducted at an NGO called Sikkola Rakyat, which carries out activities for children in Starban, Kelurahan Polonia. The purpose of this research was to analyze the role of NGOs in improving children's basic literacy through various programs, such as providing books and reading materials, training for children and parents, and implementing innovative and community-based learning methods. This study used a descriptive qualitative approach, with data collection techniques through observation, interviews, documentation, and literature study. The informants in this study consisted of key informants, namely the leaders and volunteers, primary informants, namely children who participated in activities at Sikkola Rakyat, and additional informants, namely the parents and the Head of Neighborhood X. In analyzing the role played by Sikkola Rakyat, Wills' theory was used, which defines the role of NGOs as implementers of basic literacy activities for children. As a catalyst, Sikkola Rakyat as an NGO voices the importance of basic literacy and raises public awareness. As a partner, Sikkola Rakyat as an NGO collaborates and partners with various parties to optimize basic literacy programs for children